2023
DOI: 10.3390/ma16196371
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Incremental Sheet Forming of Aluminum Alloy

Costel Catalin Coman,
Simona-Nicoleta Mazurchevici,
Constantin Carausu
et al.

Abstract: Recent developments in incremental sheet forming have resulted in the creation of novel manufacturing processes that are highly adaptable and could bring significant economic benefits for advanced technologies and low-volume production. In this manuscript, the following variables were examined: the variation in the deformation forces for a part with a pyramidal trunk shape; the variation in the deformations and thinning of the Al 3003 material during the incremental forming process; and the variation in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…In both instances, the utilized tools possessed a ball with a diameter measuring Ø 12 mm, with (53–58) HRC hardness. [ 7 ] The TiN layer has a measured hardness of ≈2300 HV, while the coating thickness ranges from 2 to 4 µm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both instances, the utilized tools possessed a ball with a diameter measuring Ø 12 mm, with (53–58) HRC hardness. [ 7 ] The TiN layer has a measured hardness of ≈2300 HV, while the coating thickness ranges from 2 to 4 µm.…”
Section: Methodsmentioning
confidence: 99%
“…The only studies are those carried out by the researchers of the present research, who identified a significant improvement of the surface characteristics with the deposition of TiN layer. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…One additional factor contributing to deviations is the utilisation of robotic systems, as opposed to milling computer numerical control (CNC) machines. As stated in references [23,45], the employment of robots might result in positional inaccuracies of the tool centre due to the elastic deformations experienced by the robot during the machining process.…”
Section: Execution Accuracy Of the Incrementally Formed Partmentioning
confidence: 99%
“…These deviations, in turn, give rise to faults in the geometric properties of the produced components. One crucial measure to address in the resolution of this issue involves incorporating appropriate compensation for the anticipated deflection in the tool path, [23,24]. The accurate estimation of the maximal forming force of the SPIF and comprehending the impact of the input parameters on this force is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…The authors optimized the tool path, speed, and step down by using a Taguchi method that considered many criteria at once. Coman and Mazurchevici [15] analyzed the context of an incremental sheet metal forming process. This study investigated how the thining of aluminum was affected by the presence of various parameters.…”
Section: Introductionmentioning
confidence: 99%